2012
DOI: 10.1007/s10068-012-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole cell biotransformation of major ginsenosides using Leuconostocs and Lactobacilli

Abstract: Various strains of Lactobacillus and Leuconostoc species were evaluated to select the most promising strain to carry out transforming major ginsenosides into minor ginsenosides. Among the experimental lactic acid bacteria (LAB), Leuconostoc mesenteroides KFRI 690, Leuconostoc paramesenteroides KFRI 159, and Lactobacillus delbrueckii KCCM 35486 produced compound K from major ginsenosides precursors (Rb1, Rc, Rd, and F2). KFRI 690 showed the best transforming activity among them. Furthermore, these LABs could bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…TLC and HPLC analysis showed that starting 2 (R f 0.25, t R 14.84 min) and its transformation product 6 were present in samples taken from bacterial suspension incubated with added 2. The R f on TLC (0.40) and HPLC retention time (t R 18.00 min) of 6 agreed with those of the standard ginsenoside known as C-O [16][17][18][19]. Like in the experiment with Rc, increasing the incubation time caused the concentration of starting 2 to decrease and the concentration of 6 to increase proportionally.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…TLC and HPLC analysis showed that starting 2 (R f 0.25, t R 14.84 min) and its transformation product 6 were present in samples taken from bacterial suspension incubated with added 2. The R f on TLC (0.40) and HPLC retention time (t R 18.00 min) of 6 agreed with those of the standard ginsenoside known as C-O [16][17][18][19]. Like in the experiment with Rc, increasing the incubation time caused the concentration of starting 2 to decrease and the concentration of 6 to increase proportionally.…”
supporting
confidence: 60%
“…BG134 on Rc was similar to that described above for Sphingopyxis sp. BG97 [14] but differed from those of microorganisms such as Actinosynnema mirum [16] and Leuconostoc mesenteroides KFRI 690 [17], which transform Rc into C-Mc and C-K, respectively, through more complete deglycosylation.…”
mentioning
confidence: 96%
“…BG78 could be used to transform principal glycoside Rc into the biologically more active minor ginsenoside (20S)-Rg 3 . This distinguished it from other Leuconostoc bacterial strains that transform Rc into other minor dammarane glycosides [3]. …”
mentioning
confidence: 92%
“…(20S)-Rg 3 differs from the principal dammarane glycosides Rb 1 , Rb 2 , Rc (1), and Rd (2) that have the aglycon protopanaxadiol only by the lack of a carbohydrate on C-20 [2]. This enables it to be produced by selective incomplete deglycosylation of these saponins, including by using various microorganisms [3,4].We reported earlier the use of several bacteria with E-glucosidase activity for transformation of ginsenoside Rb 1 into the minor glycoside F-2 and compound K [5] and Rd into the aforementioned ginsenoside (20S)-Rg 3 [6]. Herein we communicate data on the transformation of another principal glycoside, Rc (1) with a C-3 E-sophorose and a C-20 D-L-arabinofuranosyl-(1o6)-E-D-glucopyranoside, into (20S)-Rg 3 by the bacterium Leuconostoc sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation